HUBUNGAN PENGETAHUAN DAN DUKUNGAN KELUARGA DENGAN KECEMASAN MENARCHE PADA REMAJA PUTRI - Mukhoirotin, Mukhoirotin; Taufik, Milda Laila (Journal Of Holistic Nursing Science, 2016)
Abstract Menarche is an important time for a woman when puberty. Symptoms often occur during puberty is that anxiety and fear. Knowledge and family support are high is one of the forms to reduce the anxiety. The purpose of this study was to determine the relationship ofknowledge and family support with anxiety menarche in young women. The design used in this research is descriptive analytic with cross-sectional. The sample consisted of 30 respondents, the independent variable is the knowledge and family support, the dependent variable is the menarche anxiety. Sampling by using purposive sampling. Measuring devices using questionnaires, the data were analyzed using the Spearman rho test with significance level of 5% (Î± â¤0,05).The research concludes that there is a relationship of knowledge with anxiety menarche in adolescents (P = 0.002; r = - 0.544), family support relationships with anxiety menarche in adolescents (P = 0.002; r = - 0.536) with a negative correlation with the direction of considerable strength.Knowledge and family support the relationship with anxiety menarche. The higher the knowledge and family support of anxiety menarche decreased, and conversely the less than the knowledge and family support of anxiety menarche increased.